Hubungan Dukungan Suami Terhadap Tingkat Kecemasan Ibu Hamil Primigravida Trimester III Menghadapi Persalinan di Puskesmas Benu-Benua Kendari Barat - Yulli Fety Fety (PROFESSIONAL HEALTH JOURNAL, 2023)
pregnant women did not receive the support of their husbands. Whereas 1 primigravida pregnant woman was stated to have received support from her husband both in terms of emotional support, assessment, instrumental and information. This study aims to determine the relationship of the husband's support to the level of anxiety of third trimester primigravida pregnant women in the working area of the Benu-Benua Kendari West Health Center. This type of research is a quantitative study with a "Cross Sectional Study" design. The total population in April-June is as many as 31 people and a total of 31 people with the total population sampling technique. The analytical method uses the Chi Square Test. The results of this study indicate that there is a strong relationship between emotional support and P Value ≤ α (0.000 ≤ α 0.05) and Contingency Coefficient = 0.660. Contingency Coefficient = (0.4707), there is a strong relationship with instrumental support P Value ≤ α 0.05 (0.000 ≤ 0.05) and Contingency Coefficient = (0.684), there is a strong relationship with information support P Value ≤ α 0.05 (0.000 ≤ 0.05) and Contingency Coefficient = (0.707) with the anxiety level of third trimester primigravida pregnant women in the working area of the Benu-Benua Kendari West Health Center. There is a strong relationship between the husband's support and the level of anxiety of third trimester primigravida pregnant women facing childbirth in the working area of the Benu-Benua Kendari west t Health Center. The conclusion of this study is that there is a strong relationship between emotional support, assessment, instrument, and information with anxiety levels in primigravida trimester III pregnant women in the work area of the Benu benua Kendari West health center. The researchers suggested to the midwives at the Benu-Benua Health Center being able to provide information about the results of the examination and give advice to husbands if third trimester primigravida pregnant women experience problems, especially anxiety in facing childbirth. Keywords: Anxiety, husband support, primigravida,